Investigation of the heavy-ion mode in the FAIR High Energy Storage Ring - Kovalenko, Oleksandr; Dolinskii, O.; Litvinov, Yuri A.; Maier, R.; Prasuhn, D.; Stöhlker, T. (Physica scripta, 2015)
High energy storage ring (HESR) as a part of the future accelerator facility FAIR (Facility for Antiproton and Ion Research) will serve for a variety of internal target experiments with high-energy stored heavy ions (SPARC collaboration). Bare uranium is planned to be used as a primary beam. Since a storage time in some cases may be significant - up to half an hour - it is important to examine the high-order effects in the long-term beam dynamics. A new ion optics specifically for the heavy ion mode of the HESR is developed and is discussed in this paper. The subjects of an optics design, tune working point and a dynamic aperture are addressed. For that purpose nonlinear beam dynamics simulations are carried out. Also a flexibility of the HESR ion optical lattice is verified with regard to various experimental setups. Specifically, due to charge exchange reactions in the internal target, secondary beams, such as hydrogen-like and helium-like uranium ions, will be produced. Thus the possibility of separation of these secondary ions and the primary beam is presented with different internal target locations.